PROFESIONALISME GURU DALAM PENINGKATAN MUTU PENDIDIKAN - Muhammad Yunus (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
The purpose of this research is to describe the professionalism of teachers in im-proving the quality of education in SDN 65 Katteong Pinrang. This study is a qua-litative research, the data was cellected by observation, interview, and documen-tation. The data analysis technique was descriptive (non-statistical). The results of this study were: first, the professionalism of teachers in improving the quality of education in SDN 65 Katteong could be seen from four aspects of competence, namely: pedagogic, personal, social, and professional. Second, supporting factors consist of two factors, namely: internal factors and external factors. While the in-hibiting factors were: many teachers did not concentrate on their profession, the private colleges did not work properly to produce teachers candidate, this made teachers lack of motivation in improving quality of education. Third, teachers strategies to overcome inhibitors, namely: 1) learning at home; 2) studying in the library; 3) performing union of teachers; 4) involving scientific meetings 5) a for-mal learning in educational institutions; 6) participating education professional organizations meeting; and 7) involving in follow scientific competition.